Kontradiksi Implementasi Pemberdayaan KAKB (Keluarga Asuh Keluarga Binangun) Komunitas Waria (Studi Implementasi Komunitas Waria Kulon Progo di Kec. Wates, Kab. Kulon Progo) - , MUTIARA ILMA ISLAMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
KAKB (Keluarga Asuh Keluarga Binangun) is one of the answers formulation created by government Kulon Progo, to reduce the poverty. The purpose of this program will not be achieved without the active participation of the target group. KAKB program touches to the transgender community that often overlooked on other social safety nets. Empowerment is not totally eliminate the activities of transvestites to \"take to the streets\" as a musician. Besides, this study aims to find out, why they are still \"take to the streets\" as a musician in the community Transgender Empowerment KAKB. To analyze this case, the researcher uses the theory evaluation and implementation Stake Grindle, which is affected by the implementation of policy content and policy context. This research is conducted in Wates, Kab. Kulon Progo. This study uses an evaluation case study. The data collected are primary and secondary data. The retrieval using purposive and snowball methods, informants in this study include 5 members of KAKB Transgender Community and triangulate to the PKBI board (as the facilitator of empowerment), the Department of Cooperatives and UMKM Kulon Progo, Kulon Progo Posdaya Team coach, and the Agency for Community Empowerment Village Government and Family Planning, as an organizer of the program, as well as other transgender community. Data collection techniques are using observation, interviews, documentation, and book studies. The results of this research indicate a failure to change the attitude of empowerment KAKB stop singing transvestite transsexual community is located on the policy content and policy context. 1) Policy cotext shows four (PKBI Kulon Progo, Kulon Progo Regency Government, Bank Mandiri, and Posdaya) stakeholders in the processes have their individual interests. Transgender Community Empowerment close to KAKB concept of \"charity\" without the capacity development process and critical awareness. 2) The low sense of ownership towards the empowerment KAKB transvestite is caused by partial identification in government decision withdrawal (policy content). This resulted in the identification of a partial failure of transgender behavior change. 3) The fragility of commitment facilitator and companion. They look up in arms after the disbursement of funds. Evaluation design only on paper and multi-stakeholder framework on education Kulon Progo be a reason for throwing responsibility. Transgender community is considered to have empowered after receiving the money. Characteristics of institutions that is one of the spheres of influence of the failure of implementation (Grindle, 1980 hh.13-14).